One-leader and multiple-follower Stackelberg games with private information - Tomoya Nakamura (Osaka University, Institute of Social and Economic Research (ISER), 2014)
This study analyzes one-leader and multiple-follower Stackelberg games with private information regarding demand uncertainty. In the equilibrium of the Stackelberg games, a leader's private information becomes public information among followers. This study demonstrates that the strategic relationship between the leader and each follower is determined by the weight on public information regarding a follower's estimation of demand uncertainty. If the weight is sufficiently low (high), then the relationship is a strategic substitute (complement), and the leader has a first-mover (dis)advantage, respectively. In the case of strategic complementarity, the leader can exit from a market. The threshold is determined by the intensity of Cournot competition among the followers.
Keywords: C72; D82; L13; 330; Stackelberg games; Cournot games; First-mover and second-mover advantages; Public and private information